Adult‐onset Rasmussen encephalitis associated with focal cortical dysplasia. Issue 4 (26th January 2018) - Hohenbichler, Katharina; Lelotte, Julie; Lhommel, Renaud; Tahry, Riëm El; Vrielynck, Pascal; Santos, Susana Ferrao
ABSTRACT: Rasmussen encephalitis is a rare, devastating condition, typically presenting in childhood. Cases of adult‐onset Rasmussen have also been described, but the clinical picture is less defined, rendering final diagnosis difficult. We present a case of adult‐onset Rasmussen encephalitis with dual pathology, associated with focal cortical dysplasia and encephalitis. We interpreted the Rasmussen encephalitis to be caused by severe and continuous epileptic activity due to focal cortical dysplasia. The best therapeutic approach for such cases remains unclear.